Measuring The Financial Performance of Pharmaceutical Companies Listed on The Indonesia Stock Exchange Using the Dupont System - Matalata, Widi Putri; Wany, Eva (Akuntansi: Jurnal Akuntansi Integratif, 2024)
This research aims to analyze the influence of Return on Equity (ROE) on the stock prices of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2022. The study employs a quantitative approach. Data collection is conducted through document analysis, involving the gathering of annual and quarterly financial reports of pharmaceutical companies listed on the IDX throughout the specified period. Relevant secondary data can also be obtained from credible alternative sources. The analytical method utilized is the DuPont System Analysis, breaking down ROE into its fundamental components such as Profit Margin, Asset Turnover, and Financial Leverage. The research findings indicate that ROE has a significant impact on stock prices.